Implementasi Pendidikan Berbasis Life Skills Bagi Santri Pondok Pesantren - Rahmawati, Elsa Puji; Nor Laila, Azzah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to determine the concept of life skills-based education at the Al-Buruj Ngabul Jepara Islamic boarding school, the implementation of life skills-based education for students at the Al-Buruj Jepara Islamic boarding school, and supporting and inhibiting factors for the implementation of life skills-based education at the Al-Buruj Ngabul Jepara Islamic boarding school. The Al-Buruj Ngabul Jepara Islamic Boarding School is one of the Islamic boarding schools that implements life skills-based education which is aimed at providing skills to students to prepare students to face the problems that exist in society when they graduate from the Islamic boarding school. This research uses a qualitative method with a descriptive data analysis approach. Data collection techniques through interviews, observation, and documentation. Test the validity of the data through technical triangulation. The results of this research show that the implementation of life skills-based education for students at the Al-Buruj Ngabul Jepara Islamic Boarding School is beneficial for increasing the creativity and skills of students. Life skills education at the Al-Buruj Ngabul Jepara Islamic Boarding School, namely personal skills through congregational prayers, sunnah prayers, reading the Koran, dhikr, istighasah, social skills through students' daily activities and organizational activities, academic skills through religious education, khidmah and teaching practice, muhadharah in Arabic and Indonesian, vocational skills through extracurricular programs. Supporting factors are students' interests, facilities and infrastructure, and activity costs. Meanwhile, the inhibiting factors are students who lack discipline, missing equipment, and limited time.